Combined Spectroscopic and Electrochemical Detection of a NiI⋅⋅⋅HN Bonding Interaction with Relevance to Electrocatalytic H2 Production. Issue 29 (3rd June 2015) - Kochem, Amélie; O'Hagan, Molly; Wiedner, Eric S.; van Gastel, Maurice
Abstract The [Ni(PR2NR′2)2]2+ family of complexes are exceptionally active catalysts for proton reduction to H2. In this manuscript, we explore the first protonation step of the proposed catalytic cycle by using a catalytically inactive NiI complex possessing a sterically demanding variation of the ligand. Due to the paramagnetic nature of the NiI oxidation state, the protonated NiI intermediate has been characterized through a combination of cyclic voltammetry, electron nuclear double resonance (ENDOR) spectroscopy, and hyperfine sublevel correlation (HYSCORE) spectroscopy. Both the electrochemical and spectroscopic studies indicate that the NiI complex is protonated at a pendant amine that is endo to Ni, which suggests the presence of an intramolecular NiI⋅⋅⋅HN bonding interaction. Using density functional theory, the hydrogen bond was found to involve three doubly‐occupied, localized molecular orbitals: the 3dxz, 3d<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1d0p6sj3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> z 2</alternatives>, and 3dyz orbitals of nickel. These studies provide the first direct experimental evidence for this critical catalytic intermediate, and implications for catalytic H2 production are discussed.